Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Bioequivalence evaluation of risedronate sodium in healthy Chinese participants under fasting conditions: a randomized, open-label, single-dose, three-period, partial replicate crossover study - Ling He; Dan Hong; Weiyong Li; Yaping Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A subset of cell cycle regulators co-expresses with cholesterol pathway and innate immune signaling during early GCRV infection in CIK cells - Waqar Younas; Lei Zhang; Mijuan Shi; Hong Yang; Yingyin Cheng; Wanting Zhang; Yaping Wang; Xiao-Qin Xia (Fish & Shellfish Immunology, 2026)

A Survey of the Species Origins of Common Fish Cell Lines—With a Particular Focus on the Grass Carp Ovarian Cell Line ( GCO ) - Hong Yang; Mijuan Shi; Yingyin Cheng; Wanting Zhang; Bin Gui; Rong Huang; Yaping Wang; Xiao‐Qin Xia (Journal of Fish Diseases, 2026)
Cell line misidentification or contamination undermines the reliability of research outcomes. In this study, we verified the species origin of commonly used fish cell lines, with a particular focus on the grass carp ovarian cell line (GCO). RNA‐seq data from 146 samples of 11 widely used fish cell lines were collected from public databases (NCBI‐SRA) and were mapped to the reference genomes of eight species. GCO RNA‐seq samples from three Chinese laboratories showed a mapping rate of 21.64% ± 3.61% to the grass carp genome, but 89.81% ± 4.83% to the fathead minnow genome. Further transcriptomic similarity analysis revealed that these GCO RNA‐seq samples clustered more closely with cell lines originating from fathead minnow. Targeted analysis of the COI gene amplification region confirmed that nearly all reads from GCO RNA‐seq samples mapped exclusively to the fathead minnow COI amplicon. Collectively, these results indicate that GCO may have undergone cross‐contamination or species misidentification. This study raises doubts about the true species origin of the GCO cell line and proposes that COI DNA barcoding can be used to discriminate the species origin of fish cell lines.

Biogenic amines in fermented foods: A comprehensive review from formation pathways, risk analysis, detection technologies to control measures - Yaping Wang; Bing Yan; Haiqian Xu; Yanyan Huang; Qinglin Sheng; Lang-Hong Wang (Food Research International, 2026)

Highly efficient biophotoelectrochemical methanogenesis coupling with water sterilization via robust interfacial electronic communication - Jing Hu; Chaohui Yang; Yaping Qi; Mingqiu Hong; Jiajing Chen; Guoping Ren; Jie Ye (Chemical Engineering Journal, 2025)

Progress on the mechanism of natural polysaccharides in the treatment of arthritis - Lili Yuan; Michael Adu-Frimpong; Hong Chen; Yaping Yang; Jiangnan Yu; Huiya Wang; Yuxiang He; Elmurat Toreniyazov; Xia Cao; Qilong Wang; Ximing Xu (Inflammopharmacology, 2025)

The diurnal variation characteristics of warm season precipitation in Chongqing from 2011 to 2021 - Yingying Zhou; Yan Zhang; Chengzhi Deng; Qu Guo; Yaping Zhang; Yi Liu; Hong Zhang; Tingting Liu; Fan Xia (Theoretical and Applied Climatology, 2025)

ZnO nanoparticles induce melanoma-like lesions via recruiting dermal dendritic cells in barrier-damaged skin in mice - Menghan You; Yingying Huang; Yeda Chen; Dan Li; Yaping Tang; Yi kuan Du; Hong Yang; Anfa Liang; Guodong Hu; Yinghua Chen (Food and Chemical Toxicology, 2024)

Widely metabolomic combined with transcriptome analysis to build a bioactive compound regulatory network for the fruit growth cycle in Pseudocydonia sinensis - Shuangyu Zhang; Yang Wu; Yanshen Ren; Yaping Xu; Hong An; Qianyi Zhao; Yu Wang; Houhua Li (Food Chemistry, 2024)

Biochar with KMnO4-hematite modification promoted foxtail millet growth by alleviating soil Cd and Zn biotoxicity - Xirui Kang; Na Geng; Yaping Li; Wei He; Hui Wang; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; Yanhong Lou; Yuping Zhuge (Journal of Hazardous Materials, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Development of food-grade xylanase encapsulation using electrospray dextran microparticles - Yaping Zhang; Chun Liu; Yingjie Lin; Hong Wu; Ying Lin; Fengguang Zhao; Shuangyan Han (Food Hydrocolloids, 2024)

Nanocellulose based ultra-elastic and durable foams for smart packaging applications - Yang Liu; Yaping Zhu; Zijun Xu; Xin Xu; Pan Xue; Hong Jiang; Zhengjian Zhang; Meng Gao; Hongbin Liu; Bowen Cheng (Carbohydrate Polymers, 2024)

Different ligand functionalized bimetallic (Zr/Ce)UiO-66 as a support for immobilization of phosphotungstic acid with enhanced activity for the esterification of fatty acids - Qiuyun Zhang; Yaping Wu; Xingyue Hong; Zhenying Li; Yanting Lei; Rongfei Yu; Taoli Deng; Yutao Zhang; Peihua Ma (Sustainable Chemistry and Pharmacy, 2024)

Identification and analysis of alleles in the aroma biosynthesis pathways based on Camellia sinensis ‘Jinguanyin’ haplotype-resolved genomes - Mengya Gu; Ting Gao; Mengting Xu; Yaping Hong; Yibin Wang; Jiaxin Yu; Yuhang Zhang; Wenqin She; Pengjie Wang; Naixing Ye (Trees, 2023)

Soil phosphorus availability and stoichiometry determine microbial activity and functional diversity of fluvo-aquic soils under long-term fertilization regimes - Wei He; Wenhua Ye; Mingjie Sun; Yaping Li; Manman Chen; Meng Wei; Guoqing Hu; Quangang Yang; Hong Pan; Yanhong Lou; Hui Wang; Yuping Zhuge (Journal of Soils and Sediments, 2022)

Metabolite profiling in albino tea mutant Camellia sinensis ‘Fuyun 6’ using LC–ESI–MS/MS - Xinying Lin; Xuejin Chen; Pengjie Wang; Yucheng Zheng; Yongchun Guo; Yaping Hong; Ruxing Yang; Naixing Ye (Trees, 2022)

Two novel compounds from green walnut husks ( Juglans mandshurica Maxim.) - Hong Yang; Chunli Gan; Yaping Guo; Liyuan Qu; Shuang Ma; Yanbin Ren; Xingwen Wang; Libo Wang; Jian Huang; Jinhui Wang (Natural Product Research, 2020)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Removal of Trace As(V) from Water with the Titanium Dioxide/ACF Composite Electrode - Liang Peng; Yaping Chen; Hong Dong; Qingru Zeng; Huijuan Song; Liyuan Chai; Ji-dong Gu (Water, Air, & Soil Pollution, 2015)

Hepatocyte Nuclear Factor 4 Alpha and Farnesoid X Receptor Co-regulates Gene Transcription in Mouse Livers on a Genome-Wide Scale - Ann M. Thomas; Steve N. Hart; Guodong Li; Hong Lu; Yaping Fang; Jianwen Fang; Xiao-bo Zhong; Grace L. Guo (Pharmaceutical Research, 2013)

Vitreoscilla Hemoglobin (VHb) Overexpression Increases Hypoxia Tolerance in Zebrafish (Danio rerio) - Bo Guan; Hong Ma; Yaping Wang; Yuanlei Hu; Zhongping Lin; Zuoyan Zhu; Wei Hu (Marine Biotechnology, 2011)

Glacier extent and volume change (1966∼2000) on the Su-lo Mountain in northeastern Tibetan Plateau, China - Yetang Wang; Shugui Hou; Sungmin Hong; Soon Do Hur; Yaping Liu (Journal of Mountain Science, 2008)